MUC-2 human small intestinal mucin gene structure. Repeated arrays and polymorphism. - Toribara, N W (1991)
MUC-2, the first described intestinal mucin gene, has become important as a prototype for secreted mucins in several organ systems. However, little is known about its protein backbone structure and hence its role in diseases such as colon cancer, ulcerative colitis, and cystic fibrosis, which are known to have mucin abnormalities. Studies in this manuscript show that MUC-2 contains two distinct regions with a high degree of internal homology, but the two regions bear no significant homology to each other. Region 1 consists mostly of 48-bp repeats which are interrupted in places by 21-24-bp segments. Several of these interrupting sequences show similarity to each other, creating larger composite repeat units. Region 1 has no length polymorphisms. Region 2 is composed of 69-bp tandem repeats arranged in an uninterrupted array of up to 115 individual units. Southern analysis of genomic DNA samples using TaqI and HinfI reveals both length and sequence polymorphisms which occur within region 2. The sequence polymorphisms have different ethnic distributions, while the length polymorphisms are due to variable numbers of tandem repeats.